Genotyping on blood and buccal cells using loop-mediated isothermal amplification in healthy humans - Catherine Drogou; Fabien Sauvet; Mégane Erblang; Liselot Detemmerman; Céline Derbois; Marie Claire Erkel; Anne Boland; Jean François Deleuze; Danielle Gomez-Merino; Mounir Chennaoui (Biotechnology Reports, 2020)
Genetic variations contribute to phenotypic individual vulnerabilities to sleep debt, particularly for five single nucleotide polymorphisms (SNPs). Loop-mediated isothermal amplification and melting curve analysis (LAMP-MC) is a recently developed method to characterize SNPs. The aim of present study was to evaluate the LAMP-MC method on blood and buccal cells for detection of five SNPs of interest in healthy humans.We first analyzed signals obtained from LAMP-MC method on 42 samples. Then we compared the results with those of referent TaqMan method.The LAMP-MC method produced specific melting curves for the five SNPs. A high concordance of genotyping results was observed between the two methods for rs5751876_ADORA2A, rs1800629_TNF-α, rs73598374_ADA and rs228697_PER3 in blood and saliva (Cohen’s kappa coefficient >0.80). A good agreement ( = 0.61) was observed for rs4680_COMT in blood only.LAMP-MC is a simple and reliable method to study genetic influences on health, sleep debt-related performance impairments and countermeasures.